2006
DOI: 10.1155/2006/760390
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Acute Necrotizing Lung Infections

Abstract: BACKGROUND: Surgical resection for acute necrotizing lung infections is not widely accepted due to unclear indications and high risk.OBJECTIVE: To review results of resection in the setting of acute necrotizing lung infections.METHODS: A retrospective review of patients who underwent parenchymal resection between January 1, 2000, and January 1, 2006, for management of necrotizing pneumonia or lung gangrene.RESULTS: Thirty-five patients underwent resection for lung necrosis. At the time of consultation, all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 16 publications
(20 reference statements)
3
61
0
2
Order By: Relevance
“…The 15.4% rate of mortality in our study was comparable to the rates of 8–20% reported previously, and the overall outcome mainly depends on the extent of the underlying risk factors [7,10]. In this study, the 3 patients who died postoperatively and the 3 patients who developed postoperative empyema and ventilator dependency had underlying risk factors, such as corticosteroid therapy, liver cirrhosis, renal failure and COPD.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The 15.4% rate of mortality in our study was comparable to the rates of 8–20% reported previously, and the overall outcome mainly depends on the extent of the underlying risk factors [7,10]. In this study, the 3 patients who died postoperatively and the 3 patients who developed postoperative empyema and ventilator dependency had underlying risk factors, such as corticosteroid therapy, liver cirrhosis, renal failure and COPD.…”
Section: Discussionsupporting
confidence: 84%
“…When necrotizing pneumonia is extensive or complicated, and medical management is insufficient, surgical treatment has been shown to be the most successful approach [8]. Among the indications for surgery that have been proposed are bronchopleural fistula, empyema, hemoptysis, lung abscess and lung gangrene [3,9,10]. One previous report has reported on the outcome of surgical treatment in a large study group comprising 35 patients with necrotizing pneumonia; 3 of the 35 patients succumbed (8.5%) [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3,7) Chest pain, signs of respiratory distress, persistent fever, a worsening of the clinical status, and new complications secondary to pneumonia despite the use of optimal antibiotic therapy are all suggestive of pulmonary necrosis. (6,8,9) In patients meeting any of those criteria, axial chest CT is indicated, even if chest X-rays reveal no abnormalities, since chest X-rays have low sensitivity and early findings characteristic of necrotic complications are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention may be considered as an alternative treatment when the disease deteriorates or complications occur in spite of optimal medical treatment. The choice of initial antibiotics should be directed at broad coverage with commonly implicated pathogens (S. aureus, streptococci, K. pneumoniae, etc) [8]. Additional empirical anaerobic antibiotic should be considered in patients with lung abscesses.…”
Section: Picturementioning
confidence: 99%